Narrating Solidarity With Ukraine: European Parliament Debates on Energy Policy - Maria Theiss; Anna Menshenina (Social Inclusion)
The article aims to improve our understanding of the politics of energy policy in the EU in the context of the war in Ukraine. It shows how the energy policy debate is contextualised by the suffering of Ukraine and the country’s efforts to resist Russian aggression and full-scale war. An abductive qualitative content analysis of 10 European Parliament debates on economic sanctions against Russia between March 2014 and October 2022 is used to reconstruct four narratives of the EU’s transnational solidarity with Ukraine. The following solidarity narratives are compared in terms of underlying notions of solidarity, proposed policy solutions, and their temporal aspects: “solidarity based on the common enemy,” “solidarity as mutual sacrifice,” “solidarity based on shared independence,” and “solidarity based on our resilience.” We find that despite the prominence of the solidarity frame in all four narratives, there were latent relevant differences in the urgency of the proposed solutions. Moreover, the references to suffering in these narratives tend to contrast “their” and “our” suffering, rather than calling for help for Ukraine.